Laf4/Aff3, a gene involved in intellectual disability, is required for cellular migration in the mouse cerebral cortex. - Justin M Moore; Peter L Oliver; Mattéa J Finelli; Sheena Lee; Tom Lickiss; Zoltán Molnár; Kay E Davies (PLoS ONE)
Members of the AFF (AF4/FMR2) family of putative transcription factors are involved in infant acute leukaemia and intellectual disability (ID), although very little is known about their transcriptional targets. For example, deletion of human lymphoid nuclear protein related to AF4/AFF member 3 (LAF4/AFF3) is known to cause severe neurodevelopmental defects, and silencing of the gene is also associated with ID at the folate-sensitive fragile site (FSFS) FRA2A; yet the normal function of this gene in the nervous system is unclear. The aim of this study was to further investigate the function of Laf4 in the brain by focusing on its role in the cortex. By manipulating expression levels in organotypic slices, we demonstrate here that Laf4 is required for normal cellular migration in the developing cortex and have subsequently identified Mdga2, an important structural protein in neurodevelopment, as a target of Laf4 transcriptional activity. Furthermore, we show that the migration deficit caused by loss of Laf4 can be partially rescued by Mdga2 over-expression, revealing an important functional relationship between these genes. Our study demonstrates the key transcriptional role of Laf4 during early brain development and reveals a novel function for the gene in the process of cortical cell migration relevant to the haploinsufficiency and silencing observed in human neurodevelopmental disorders.